JURIDICAL ANALYSIS OF THE ASEAN AGREEMENT ON TRANSBOUNDARY HAZE POLLUTION AND ITS IMPLEMENTATION IN INDONESIA - Miftah Ramadhan (Faculty of Law Universitas Lampung, 2019)
The Trans-boundary Haze Pollution in the international environment scope is not an uncommon problem to be face nowadays. The case that leads to the controversy of how to solve and to decide which party to responsible brings states over the world to have a significant concern in the case to make a new regulation on cross-border smoke pollution. The method used in this paper is a juridical-normative comparative legal research method. The result shows that in international scope both of ASEAN Agreement on Transboundary Haze Pollution (AATHP) and Rio Declaration is not complete enough to handle the case of the trans-boundary haze pollution problem. Therefore, a legal framework is needed to support the international and national regulation concerning on environment.